Legal Security and Legal Protection Of Outsourcing Employees Based On Indonesian Labor Law - Mofea, Sukhebi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Outsourcing practices are a serious concern in discussions of employment in Indonesia because almost all companies rely on outsourced labor to maintain their competitiveness in a rapidly changing global economy. This research method uses normative legal research using a literature study approach to analyze the data used in this article. The aim of the research in this article is to examine the regulation and implementation of outsourcing from a labor law perspective, as well as to examine legal certainty and protection for the implementation of labor using an outsourcing system in companies. The results and discussion in this article are that in the field of employment law, outsourcing can be implicitly found in the provisions of Law Number. 13 of 2003 concerning Employment. One form of legal protection and certainty, especially for workers, is through the implementation of work agreements. An employment agreement is an agreement made between the employer and recipient of employment and is the starting point for an employment relationship, which contains employment conditions that refer to Law Number 13 of 2003 on Employment.Keywords:Legal certainty; Legal Protection; Outsourcing Labor; Employment Law